The Augmented Reality Based Flashcards for Learning Heat and Thermodynamics in High School - Siahaan, Sardianto Markos; Putri, Regita Elsa (Jurnal Penelitian & Pengembangan Pendidikan Fisika, 2024)
The objective of this study is to create augmented reality flashcards for teaching heat and thermodynamics to 11th grade students. These flashcards will be used in the classroom during learning sessions for 11th grade science students. The work was executed utilizing the Alessi and Trollip methodology, which encompasses the stages of planning, design, and development. The data were obtained by means of expert validation and a response questionnaire. The findings indicated that the material had a validity rate of 92% and fell into the category of being highly valid. Similarly, the media had a validity rate of 86.95% and also fell into the highly valid category. Therefore, the product gets a validity rating of 89.47% and falls into a very valid category. The practicality score during the first stage of the beta test was 89.2%, with a specific focus on the practical category and a sample size of 4 students. In the second stage of the beta test, the practicality score decreased to 86.27%, with the same focus on the practical category but with a larger sample size of 10 students. The teacher's answer to the practical category yielded a score of 87%. Therefore, the flashcard product utilizing augmented reality for the subject of heat and thermodynamics in the 11th grade of high school could be used for learning purposes.